EFEK BAHAN PEMBAWA PADA BEBERAPA SUHU PENGERINGAN BIOFUNGISIDA PELET Trichoderma pseudokoningii Rifai TERHADAP JAMUR Ganoderma boninense Pat SECARA IN VITRO - Tambunan, Reisyi Rinola; Elfina S, Yetti; Ali, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objective of the research is to study the effect of carrier materials on various drying temperatures of biofungicide granule T. pseudokoningii Rifai on               G. boninense Pat. in vitro. The research has been conducted at Plant Disease Laboratory of Agricultural Faculty and Nanotechnology and Material Laboratory of Department of Physics, Mathematics and Science Faculty, University of Riau from May 2013 to August 2013. This research has been conducted experimentally using split plot design arranged in a completely randomized design, consisted of 9 combined treatments and each treatment is repeated 3 times. Main plot is drying temperatures of biofungicide granule (T), consisted of 3 levels : T1 = 350C, T2 = 550C, T3 = 750C. Sub-plot is carrier materials of biofungicide granule (P), consisted of 3 levels : P1 = Kaolin, P2 = Zeolite, P3 = Kaolin + Zeolite. The data were statistically analyzed using analysis of variance and further analyzed with Duncan's New Multiple Range Test (DNMRT) at level 5%. The results of the research showed that kaolin, zeolite and combination of kaolin and zeolite containing in biofungicide granule of T. pseudokoningii on drying temperature of 550C gave a better result to press the growth of G. boninense, because                            T. pseudokoningii has faster growth rate, that is 3.01 mm/day.   Keywords: Biofungicide granule Trichoderma pseudokoningii, carrier materials, drying temperatures, Ganoderma boninense.